Aryne-induced dearomatized phosphonylation of electron-deficient azaarenes. Issue 40 (6th April 2016) - Liu, Kai; Liu, Li-Li; Gu, Cheng-Zhi; Dai, Bin; He, Lin
Abstract : Aryne-induced dearomatic phosphonylation of electron-deficient azaarenes. Abstract : An aryne-induced dearomatized phosphonylation reaction has been developed. Electron-deficient azaarenes such as quinolines, isoquinolines, phenanthroline and acridine undergo multicomponent reaction with arynes and dialkylphosphites to afford the corresponding dearomatized phosphonylated heterocycles in 50–90% yields.